Nurse practitioners in home health care: an update - Neal‐Boylan, Leslie; Mager, Diana; Kazer, Meredith Wallace (Home Health Care Management & Practice, 2012)
Nurse practitioners are playing an increasingly visible role in home care. The Institute of Medicine in collaboration with the Robert Wood Johnson Foundation recommends wider use of Advanced Practice Registered Nurses and there has been growing interest in using the role in home care.1 However, the physician remains the provider who must sign home health agency paperwork and orders. The "Home Health Care Planning Improvement Act" would allow nurse practitioners to certify Medicare-sponsored treatment plans.2 This article will discuss the status of the nurse practitioner role in home care, the impact of reimbursement on home care services, how the passage of the new act would change current practice, and a vision for the future role of the nurse practitioner in home health care. © 2012 SAGE Publications.
Keywords: Home Health Care Improvement Act; conceptual model; dept.nur; home health care; nurse practitioner; transitional care model

After the gap analysis: Education and practice changes to prepare nurses of the future - Beauvais, Audrey Marie; Kazer, Meredith Wallace; Aronson, Barbara; Conlon, Suzanne E.; Forte, Pamela; Fries, Kathleen S.; Hahn, Judith M.; Hullstrung, Russell; Levvis, Meg; McCauley, Paula; Morgan, Patricia Padula; Perfetto, Linda; et al. (Nursing Education Perspectives, 2017)
AIM The purpose of the study was to describe the Connecticut Nursing Collaborative-Action Coalition’s work in identifying and addressing gaps between nursing education and practice based on the Institute of Medicine’s Future of Nursing report. BACKGROUND Massachusetts Nurse of the Future (NOF) Competencies highlight the knowledge, skills, and attitudes/behaviors required for professional nurses. Integrating these concepts into the educational system will prepare the nursing workforce to respond to current/future health care needs and population health issues. METHOD Education and practice partners in four regions conducted a gap analysis of the education to practice transition for new graduate nurses using NOF as a framework for assessment. RESULTS Gaps in competencies were similar across regions. However, each organization uniquely addressed curricular gaps to best prepare nurses of the future. CONCLUSION Curriculum improvements will provide students the advantage of being prepared for the rapid changes happening in health care. Copyright © 2017 National League for Nursing
Keywords: Academic-Practice Partnership; Connecticut; Curriculum; Education, Nursing; Forecasting; Future of Nursing Competencies; Gap Analysis; Humans; Massachusetts; New Graduate Nurses; Nursing Curriculum; Nursing Education; Nursing Staff; article; curriculum; dept.nur; forecasting; health care need; human; human experiment; nursing education; nursing staff; peer-reviewed; population health; skill; student; workforce